STRATEGI MANAJEMEN PROGRAM LITERASI SEKOLAH DALAM UPAYA MENINGKATKAN KUALITAS PENDIDIKAN DI UPT SATUAN PENDIDIKAN SDN KALIREJO BANGIL. - Khoirin Nisak; Suyanto Suyanto; A. Faizin (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze the management strategies of the school literacy program in improving educational quality at UPT SDN Kalirejo Bangil. The research explores how the four key management functions—planning, organizing, actuating, and controlling—are implemented to cultivate a sustainable literacy culture in a primary school setting. Employing a qualitative case study design, the study involved five key participants, including the principal and four teachers from different grade levels. Data were collected through in-depth interviews, participatory observations, and document analysis, and were examined using Miles and Huberman’s interactive model. The findings reveal four major themes: (1) literacy planning is carried out collaboratively and aligned with class needs; (2) the organizational structure supports program implementation through a clearly defined literacy team; (3) program execution includes various innovative activities such as 15-minute reading routines, reading journals, literacy boards, and book discussions; and (4) evaluation remains basic but is useful for monitoring students’ literacy progress. These findings highlight the importance of instructional leadership, teacher collaboration, and a supportive literacy environment. The study implies the need for enhancing teachers’ literacy competencies, increasing resource availability, and developing more systematic evaluation mechanisms.